Vous êtes sur la page 1sur 2

# 1

3x
1 ln x

= )f ( x

(b

f ( x ) = ln ( ln x ) (c

(d

(a

2
-1

-1 f f
-2 f

-3

f ( x ) = ln 2 x 2 x + 3
2

-4 C f 1

) f ( x ) = 1 ( ln x

x
f
x +1
8
f

f ( x) = ln

ln ( 2x 3)( x + 1) = ln 3 ; ln ( 2x 3) + ln ( x + 1) = ln 3

ln 2x 3 + ln x + 1 = ln 3 ; 2ln ( 2x 1) 3ln (1 x ) = 0

-2
x + 2
ln
0
x 1

) f ( x ) = x(1 ln x
x 0

f ( 0 ) = 0
-1 D f ) lim f ( x f
2

ln 3x 2 + x + 2 0
ln x + 1 ln 3 x + 5

x +

2 ( ln x ) + 3 ln x = 0
2

0
-2 f 0

-3 f

) ( ln x

1
+ Log 4 ( 2 x + 5 ) + Log 4 2
2
3
= )Log 2 x + 2 + Log 4 ( x + 3
2
3

Log x e + Log y e = 2
-4 2

3
= ln xy

2
3

= Log 2 x

) lim x ( ln x

lim x + ln x 2 + 1

lim x(ln x) n

lim ( sin x ) ln x

x 0+

x 0+

x2 2x

lim ln

x2 + 3
x 3
lim x ln

x +
x

-4 C f
-5 C f ..
9

f x 1
-1 D f ) lim f ( x
x 1

-4 C f

x 0+

x+2

-5 C f A

lim

A
-6 C f

x +

lim ( ln x ) x
2

-7 C f

x +

(1
(3

3+ x
4x
ln x

1 (ln x) 2

= )f ( x

; (4

(5

0, 7

ln 2

10
f

) f ( x ) = ln (1 ln x

; (2

; ) lim f ( x

x +

f
-3 f 0

ln x 2 + 2

f ( x ) = ln

-2 ) f ' ( x x } D f {0

4
) f ' ( x

f ( x ) = ln

C f ..

-3

f ( x) = 0

f ( x ) = ln 2 x x + 1

f ( x ) = ln x + x + 1
2

-1 D f ) lim f ( x ) lim f ( x

x +

-2 f

1 + ln x

x 0
= ) f ( x
1 ln x

f ( x) = x 1
x0

-3 C f
-4 C f ..

5
2
x
f f ( x) = + ln
2
x
6
f

-5 C f

x + 1 + x2 = 1

x + 1 + x2

f ( x ) = ( ln x ) ln x
2

http://arabmaths.ift.fr

www.Lycee4.com

Moustaouli Mohamed

## Pour plus, visitez le site Web suivant

11

f :

x2
x+2

14
f x

f ( x) = x + 2 + ln

1
:
f ( x) = 1 + ln x
x
(1 . f . D f

C ) ( o; i; j
(1 D f f

(4 C f
(5

+
+

C ) ( o; i; j

) ( o; i; j

. Dg . g g

ln x + 1

x0
= ) f ( x
1 ln x

f ( 0 ) = 1

. Dg

. (x Dg ) : g '( x) = f ( x) :
. . g
. ) (C g ) (

0 .
f 0
.
(2 ) f ' ( x x . D f

y = x 1
. ) . (C g

15
(I h x
x
= ) h( x
+ ln( x + 1) :
x +1
(1 Dh h . Dh

(3 C f I
. C f . I

C f

(2 . ) h '( x x Dh .
. h ). h( x
) ( h(0) = 0
. (II f x

13
f x :

)f ( x) = ln( x3 3x + 2

C ) ( o; i; j

(1 ( x 1) 2 ( x + 2) : . D f

. (2 . C f

(3 f

(3 . f x0 = 0
.
. ) f '( x x D f x 0

(4 . [ x ]1; + :

3
2

f ( x) = 3ln x + ln 1 2 + 3
x
x

. . C f

) f '( x )h( x
. f

. C f
. ) f (2

http://arabmaths.ift.fr

www.Lycee4.com

)f ( x) = x ln( x + 1

. (1 D f f . D f

(2 f . D f

. ) (C g . o; i; j

. x0 = 0

g ( x) = ( x 1) ln x

) (C g

(1 D f . f

. x

. f
. ) f (1 ). f ( x
(2 g x

C f ) ( 2cm

x
*
+

12
f x
:

*
+

. ) f '( x

(2 ) I ( 0; 2 C f
(3 f

*
+

. C f ). o; i; j " f

[]1; 0

C ) ( o; i; j

[.( ]0; +

Moustaouli Mohamed